Evaluation of biocompatibility of the copolymer of 2-hydroxyethyl methacrylate with 2-(methylsulfanyl)ethyl methacrylate - Prádný, Martin; Petrovický, Pavel; Fronková, Václava; Vacík, Jirí; Smetana, Karel (Journal of materials science. Materials in medicine, 2002)
This study compares subcutaneous and intracerebral biocompatibilty of two hydrogels: copolymer of 2-hydroxyethyl methacrylate with 2-(methylsulfanyl)ethyl methacrylate and poly(2-hydroxyethyl methacrylate) as reference polymer. The experimental copolymer was more biologically inert than poly(2-hydroxyethyl methacrylate) in both the studied parameters, hence the former material is a suitable candidate for biomedical application.